New directions in participatory plant breeding for eco-efficient agriculture = Nuevas direcciones en el fitomejoramiento participativo para la agricultura eco-eficiente - Biermayr Jenzano, Patricia (International Center for Tropical Agriculture, 2010)
Farmers across the globe are facing unprecedented changes in their environment. Climate change is affecting the natural environment in often catastrophic and unpredictable ways. The global economic 'bubble'; that provided cheap credit to many people has burst. The individual and combined effects of these two events are driving the poor into even greater poverty. Resource-poor farmers need strategies to be able to adapt to the changing conditions, over and above their ongoing efforts to raise themselves to a higher state of well-being out of poverty. As the effects of climate change are increasingly felt worldwide, especially in the humid and semi-arid tropics, dry areas; and other regions with extreme; climates;there is an increasing need for crop breeding and variety development to become more adapted to changing weather events while making production more efficient. In this case, efficiency; is not measured simply as the ability to churn out new varieties of staple crops, but for the work to be responsive to farmers; (rapidly) changing needs and in specific circumstances. To this end, the Program on Participatory Research and Gender Analysis (PRGA Program) is experimenting with, promoting, and advocating new directions in participatory plant breeding (PPB) to equip both small-scale farmers and researchers for the challenges ahead.